THE LEVEL OF AWARENESS OF GUIDANCE AND COUNSELLING AT KOMENDA COLLEGE OF EDUCATION - Arkorful, Paul; Adam-Yawson, Nana; Insaidoo, Sylvester (American Journal of Education and Practice, 2021)
Purpose: This study explored the nature of guidance and counselling services available for the students in Komenda College of Education. Methodology: The descriptive survey design was used for the study. A sample of 185 students consisting of 95 level 200 students and 90 level 300 students were sampled from the population. The major instrument used for data collection was questionnaire. Questionnaire was used because it is the most appropriate instrument that could be used to collect data on the variables for the study. Content-related evidence of validity was established for the instrument. The researchers personally administered the questionnaire. The entry of quantitative data and analysis was done using Statistical Package for the Social Sciences (SPSS). Findings: The results from the study showed that guidance and counselling services were vibrant and visible in Komenda College of Education. The study revealed that Seventy-five per cent (75%) of the respondents claimed that attitudes of Guidance and Counselling Coordinators and Tutors were very appropriate for counselling services. All types of guidance and counselling services were rendered in the college. The study further revealed that some students had negative attitudes towards accessing guidance and counselling services. Unique Contribution to Practice and Policy: The researchers therefore recommend that, school authorities should be provided with needed logistics for effective guidance and counselling services in schools and colleges. Also, there should be in-service trainings and refresher courses and seminars for guidance and counselling coordinators to up-date their skills in guidance and counselling. Finally, the Ghana Education Service should organise periodic educational programmes for both teachers and students on the role of guidance and counselling in schools and colleges.